'Time to Ponder': Professional Learning in Early Childhood Education. Issue 1 (March 2014) - Whitington, Victoria; Shore, Sue; Thompson, Carol
EARLY CHILDHOOD TEACHER KNOWLEDGE and professional capacity is critical to the achievement of the goals of the Council of Australian Governments' (COAG) early childhood policy agenda. This paper reports on a study of the professional development challenges that faced 87 preschool teachers at a time of major policy change. Employing Dorothy Smith's (2005) notion of 'generous work', a university upgrade program was designed to map teachers' existing skills and knowledge against four-year graduate proficiency standards. Teachers experienced substantial challenges to their identities as competent professionals as they re-entered the 'modern' university learning environment. Lecturers noticed that teachers had difficulties in re-engaging in study and articulating their practice using early childhood education theory and policy. The study concluded that to engage effectively in ongoing professional learning and so build 'extended professionalism' teachers require inbuilt 'slow time'. Implications for cross-sectoral partnerships are also included.